The summaries on the death of Jesus in Mark. Archbishop Romero, "martyr for hatred of the faith" - Acosta Bonilla, Manuel de J. (Revista Latinoamericana de teología, 2015)
No abstract available. Revista latinoamericana de teología, Vol. 32, No. 95, 2015: 175-199.